2020
DOI: 10.18502/keg.v5i6.7036
|View full text |Cite
|
Sign up to set email alerts
|

Airflow and Thermal Behavior within Peaches Packaging Box Using Computational Fluid Dynamics - A Preliminary Study

Abstract: Post-harvest cold storage of peaches is an essential element to maintain the quality of the fruits without any loss. This work aims to present a CFD model, to predict airflow patterns and temperature profiles in ventilated packaging systems, during the forced-air cooling of Peaches stored in a cold chamber. Transient CFD simulations are performed for the chamber containing four ventilated boxes and the evaluation of the results show that the temperature removal near the vent holes and the hand holes is relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The boxes vary only in the size, position, and shape of the vent holes. This numerical study continues the analysis started in previous works [30][31][32][33][34] where the evaluation of different fruit packaging box designs was developed, leading to a set of best performance packaging boxes. This study presents the multi-parameter approach using transient CFD models of the three best different packaging boxes with different vent shape, size, and location to predicts the airflow and temperature distribution during the cooling phase.…”
Section: Introductionsupporting
confidence: 70%
“…The boxes vary only in the size, position, and shape of the vent holes. This numerical study continues the analysis started in previous works [30][31][32][33][34] where the evaluation of different fruit packaging box designs was developed, leading to a set of best performance packaging boxes. This study presents the multi-parameter approach using transient CFD models of the three best different packaging boxes with different vent shape, size, and location to predicts the airflow and temperature distribution during the cooling phase.…”
Section: Introductionsupporting
confidence: 70%
“…In this paper, a study of 3 packages with fruit models that replicate the properties of real fruits was performed. These three new packages were selected from prior numerical studies [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…This prediction shows that the numerical results are consistent with the experimental work and that slight discrepancies are acceptable with the different parameters controlling the simulation and experiment. Some research work [5,28,[31][32][33] suggested these differences are admissible. Furthermore, to have more insight into the thermal performance within the packaging box, the temperature of the fruit model in each packaging box is studied, and the results are compared with the experimental data, as shown in Figure 8.…”
Section: Temperature Distribution Within Different Packaging Box Configurationmentioning
confidence: 99%
“…This prediction shows that the numerical results are consistent with the experimental work and that slight discrepancies are acceptable with the different parameters controlling the simulation and experiment. Some research work [5,28,[31][32][33]] suggested these differences are admissible.…”
Section: Temperature Distribution Within Different Packaging Box Configurationmentioning
confidence: 99%